Analisis Tingkat Kebisingan di Sekitar Gerbang Kampus Universitas Bengkulu - Fades Br Gultom; Refpo Rahman; Heriansyah Heriansyah (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2022)
The purpose of this study was to determine the level of noise that occurred around the entrance and exit gates of the south and west of Bengkulu University. Noise level measurements will be carried out using a sound level meter type GM 1356 with a measurement range between 30-130 dB(A) or 35-130 dB(C). The research method used a descriptive analysis with data collection techniques by systematic purposive sampling. Sound intensity data at the entrance and exit of the south and west gates were recorded in the time range 7.00-7.30, 7.30-8.00, 8.00-8.30, 11.15-11.45 and 13.00-13.30 WIB for four days. The results showed that the equivalent sound pressure level during the day (Ls) was 64.98 dBA, 66.47 dBA, 65.2 dBA, 63.69 dBA. The data shows a decrease in sound intensity in the time range of 8.00-8.30 WIB, which is 56.1 dBA. The average data has exceeded the threshold value of school noise quality standards and the like, which is 55 dBA. So it is necessary to take countermeasures to anticipate the emergence of communication, hearing and psychological disorders in both the campus community and the community outside the campus.